What to say next - Buxbaum, Julie (2017)
When an unlikely friendship is sparked between relatively popular Kit Lowell and socially isolated David Drucker, Kit asks David for his help figuring out the how and why of her father's tragic car accident.
Keywords: Friendship -- Fiction; Friendship -- Fiction; Love -- Fiction; Love -- Fiction; Grief -- Fiction; Grief -- Fiction; High schools -- Fiction; High schools -- Fiction; School stories; Schools -- Fiction; Friendship -- Juvenile fiction; Friendship -- Juvenile fiction; Love stories; Romance fiction; Grief -- Juvenile fiction; Grief -- Juvenile fiction; High schools -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Schools -- Juvenile fiction